Study on the changes in physical and chemical properties of red basalt soils under different utilization types of Daknong province - Anh, Luu The; Thanh, Nguyen Đuc; Lịm, Duong Thi Thanh; Huong, Nguyen Lan; Hue, Nguyen Thi; Huong, Nguyen Hoai Thu (Vietnam Journal of Earth Sciences, 2014)
National use of soil resources is one of the measures for agricultural sustainable development. In recent years, the unplanned and unreasonable development of long-term industrial trees and annual crops has to lead to red basalt soil fertility decline and physical and chemical deterioration in Daknong province. The research results showed that the nutrient content of red basalt soil under different land utilization types has been declined sharply. The declining level of organic matter content of topsoil (0 - 20cm) in annual cropland is 64.5%, pine plantation land is 55.2%, pepper cultivation land is 53.6% and coffee cultivation land is 27.8% in comparison with natural forest land. The value of cation exchange capacity (CEC), the concentration of total substances and easily digestible nutrients under land utilization types have also significantly reduced as compared to natural forest land.